PALM OIL EXPORTS - IMPORTS BETWEEN INDONESIA AND MALAYSIA BASED ON THE PERSPECTIVE OF ABSOLUTE ADVANTAGE THEORY - Delina Stia Wahyuaristy; Muhammad Khoiril Akhyar (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
The foreign exchange earnings of countries in Southeast Asia, especially Indonesia and Malaysia, mostly come from one of the main agricultural commodities, namely palm oil. Domestic palm oil production intended to meet palm oil needs in Indonesia has been fulfilled without the need for contributions from other countries. Thus, there is a surplus between palm oil production and domestic palm oil needs, so that the surplus can ultimately be exported to meet demand for palm oil from other countries. The challenge faced by Indonesia in exporting palm oil to other countries is that the number of Indonesian palm oil derivative products is still inferior to Malaysia which has around 250 derivative products. This is of course a big challenge, considering that Indonesia is the main country producing palm oil, but in reality, Indonesia has not been able to process palm oil derivative products which have a higher selling value on the international market. This research was conducted using a normative juridical method with a comparative approach and a conceptual approach and analysed using the theory of absolute advantage. In the context of this paper, it is interesting when the absolute advantage theory is used in analysing the superiority of Indonesian and Malaysian palm oil exports and imports within the scope of international trade law. Challenges in the absolute superiority between Indonesia and Malaysia in international trade, both from within the country, in the form of competition for land between oil palm plantations, local communities and traditional rights owners, often give rise to land and foreign conflicts in the form of anti-deforestation policies implemented by European Union (EU) countries which prohibit CPO imports as a step to increase the use of renewable energy which is considered more environmentally friendly.